Cosmetic brush with bionic touch and high powder holding force and manufacturing process thereof
Patent Information
- Application Number
- CN202611314255.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的是提供一种兼顾仿生触感与高抓粉力的化妆刷及其制作工艺,旨在解决如何在不牺牲合成纤维柔软弹性的前提下,显著提升其抓粉力和匀粉能力,并使刷头中心上色集中、边缘晕染过渡自然的问题,从而获得接近甚至超过天然动物毛刷的综合使用性能
[0016] This invention provides a makeup brush and its manufacturing process that combine a biomimetic feel with high powder-grabbing power. By using non-circular cross-section fibers, the specific surface area is increased, enhancing the contact area between powder and fibers. Chemical etching creates submicron-level micropores and protrusions on the fiber surface, mimicking the microstructure of animal hair scales, enhancing the mechanical locking force and van der Waals forces between powder particles and fibers, thus significantly improving powder-grabbing power. The difference in tip length formed by mixing three sets of fibers of different lengths creates a natural conical shape for the bristles, improving the uniformity of powder pickup and release. The design of a pore array density decreasing from the center to the edge results in dense bristles and concentrated powder pickup in the central area of the brush head, while the bristles are sparse and release powder gently in the edge area, achieving a natural blending effect. These four synergistic effects combine to achieve the difficult-to-achieve balance between a soft skin feel, a biomimetic feel, high powder-grabbing power, and natural blending in a synthetic fiber brush.
Smart Images

Figure CN122911233A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of makeup brush manufacturing technology, and in particular to a makeup brush that combines a biomimetic feel with high powder-grabbing power, and its manufacturing process. Background Technology
[0002] As a core category of makeup tools, the performance of makeup brushes is primarily determined by the bristle material, bristle structure, and bristle density. Natural animal hair (such as goat hair, squirrel hair, and weasel tail hair) has long been considered the preferred material for high-end makeup brushes due to its microscopic scaly structure, naturally tapering tips, and natural gradient in bristle density. This allows for excellent powder pickup, a soft feel against the skin, and natural blending transitions. However, animal hair has drawbacks: unstable sourcing, high price, a tendency to cause skin allergies, difficulty in thorough cleaning, and conflict with animal welfare principles.
[0003] Therefore, to replace animal hair, current technologies generally use synthetic fibers such as polybutylene terephthalate (PBT) and polyamide (PA). Conventional synthetic fibers typically have a circular cross-section, a smooth surface, and a small specific surface area, resulting in weak adhesion of powder particles to the fiber surface. This necessitates repeated application, leading to low makeup application efficiency. Reducing the fiber diameter to increase softness significantly decreases the fiber's resilience and stiffness, causing the brush head to collapse during use and making it difficult to control the pressure. Furthermore, existing synthetic fiber makeup brushes typically have uniform bristle length and a consistent bristle density distribution. The difference in powder pickup and release speed between the center and edge areas of the brush head is minimal, making it impossible to simultaneously achieve both high color application efficiency and a natural blending effect at the edges.
[0004] To address the aforementioned issues, some existing technologies attempt to modify synthetic fibers, such as applying alkali reduction treatment to the fiber surface to create a rough surface, or using irregularly shaped fibers to increase the specific surface area. However, single modification methods often only improve one aspect of performance and cannot simultaneously achieve a comprehensive effect of softness, biomimetic touch, high powder-grabbing ability, and natural blending. Furthermore, existing processes lack systematic optimization of the bristle length combination and the arrangement of the bristle pore array, failing to solve the problem of coordinated color application and blending at the overall structure level of the brush head.
[0005] Therefore, it is necessary to provide a makeup brush and its manufacturing process that combine a biomimetic feel with high powder-grabbing power to overcome the above-mentioned defects. Summary of the Invention
[0006] The purpose of this invention is to provide a makeup brush that combines a biomimetic feel with high powder-grabbing power and its manufacturing process. It aims to solve the problem of how to significantly improve the powder-grabbing power and powder-spreading ability without sacrificing the softness and elasticity of synthetic fibers, and to make the color concentrated in the center of the brush head and the edge blending naturally, so as to obtain the comprehensive performance of a brush that is close to or even exceeds that of a natural animal hair brush.
[0007] To achieve the above objectives, the present invention provides a manufacturing process for a makeup brush that combines a biomimetic tactile feel with high powder-grabbing power, comprising the following steps: S1. Polybutylene terephthalate is blended with polyamide and melt-spun to obtain fibers with a non-circular cross section. S2. Perform surface chemical etching on the fiber to form micropores with a depth of 0.2μm~1.0μm on the fiber surface, and make its surface roughness 0.7μm~1.8μm; S3. The fibers after surface chemical etching are cut into three groups of fibers of different lengths, mixed, combed and clumped together to form hair bundles with a length difference of 0.5 mm to 2.0 mm at the tip. S4. The bristle bundles are implanted into a mold with a pore array whose density decreases from the center to the edge. The roots of the bristle bundles are then dipped in moisture-curing polyurethane hot melt adhesive and cured to form a brush head. The pore density in the central region of the mold is 7-9 pores / cm², and the pore density in the edge region is 4-5 pores / cm². S5. Press the brush head into the inlet tube, and then perform low-temperature freezing, shaping, cleaning, and disinfection to obtain a makeup brush.
[0008] In a preferred embodiment, in step S1, the mass ratio of polybutylene terephthalate to polyamide is 75:25 to 82:18, the non-circular cross-section is wavy or trilobal, the melt spinning temperature is 250°C to 280°C, and the stretching ratio is 3.2 to 4.0 times, so that the diameter of the obtained fiber monofilament is 0.06 mm to 0.12 mm.
[0009] In a preferred embodiment, in step S2, when performing surface chemical etching on the fiber, the treatment solution used contains, by mass percentage: 2wt%~4wt% sodium hydroxide, 0.3wt%~0.8wt% fatty alcohol polyoxyethylene ether, 0.5wt%~1.2wt% γ-aminopropyltriethoxysilane, with the balance being water; the immersion temperature is 65℃~75℃, and the time is 18min~30min; wherein, the average etching depth h satisfies the following relationship with the immersion time t and temperature T: In the formula, h is the average etching depth in μm; k is a preset constant related to the fiber material and alkali concentration; t is the immersion time in min; Ea is the apparent activation energy; R is the molar gas constant; T is the absolute temperature in K.
[0010] In a preferred embodiment, in step S3, the length and mass percentage of the three groups of fibers are as follows: the length of the long fiber group is 35mm~38mm, accounting for 50%~60% of the total mass of the fiber bundle; the length of the medium fiber group is 32mm~35mm, accounting for 20%~30% of the total mass of the fiber bundle; and the length of the short fiber group is 28mm~32mm, accounting for 15%~25% of the total mass of the fiber bundle. The mixing time of the three groups of fibers is 5min~8min, the mixing air velocity is 1.5m / s~2.5m / s, and after mixing, the fibers are combed and tucked to form a fiber bundle.
[0011] In a preferred embodiment, in step S4, the diameter of each hole in the aperture array is 0.6 mm to 1.0 mm, and the radial distribution of the aperture density satisfies: In the formula, ρ(r) is the pore density at a distance r from the center of the brush head, in units of pores / cm². 2 ;ρ c The pore density in the central region of the mold is 7~9 pores / cm³. 2 ;ρ e The pore density in the edge region of the mold is 4~5 pores / cm². 2 R is the equivalent radius of the brush head, in mm; n is the gradient exponent, ranging from 1 to 2.5.
[0012] In a preferred embodiment, in step S4, the hair tuft is implanted into the mold at a depth of 4 mm to 7 mm, the root adhesive layer thickness is 0.3 mm to 0.5 mm, the curing temperature is 105℃ to 115℃, the relative humidity is 40% to 60%, and the curing time is 6 min to 10 min.
[0013] In a preferred embodiment, step S5, the low-temperature freezing trimming includes: placing the brush head in a -10℃~0℃ freezing chamber for 15min~25min to stiffen the fibers; then trimming with a rotary cutter at a speed of 3000rpm~5000rpm and a feed speed of 2mm / s~5mm / s, with the trimming error set to ≤±0.3mm; and then warming up for 10min~15min after trimming.
[0014] In a preferred embodiment, step S5, the cleaning and disinfection includes: ultrasonic cleaning at a frequency of 28 kHz to 40 kHz for 2 min to 4 min, the cleaning solution containing 0.05 wt% to 0.1 wt% of a neutral surfactant; then disinfecting with ozone at a concentration of 5 ppm to 10 ppm for 30 min; and finally drying under hot air at 40℃ to 50℃ until the moisture content is less than 0.5%.
[0015] The present invention also provides a makeup brush that combines a biomimetic feel with high powder-grabbing power, which is manufactured by the manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power as described in any of the above embodiments.
[0016] This invention provides a makeup brush and its manufacturing process that combine a biomimetic feel with high powder-grabbing power. By using non-circular cross-section fibers, the specific surface area is increased, enhancing the contact area between powder and fibers. Chemical etching creates submicron-level micropores and protrusions on the fiber surface, mimicking the microstructure of animal hair scales, enhancing the mechanical locking force and van der Waals forces between powder particles and fibers, thus significantly improving powder-grabbing power. The difference in tip length formed by mixing three sets of fibers of different lengths creates a natural conical shape for the bristles, improving the uniformity of powder pickup and release. The design of a pore array density decreasing from the center to the edge results in dense bristles and concentrated powder pickup in the central area of the brush head, while the bristles are sparse and release powder gently in the edge area, achieving a natural blending effect. These four synergistic effects combine to achieve the difficult-to-achieve balance between a soft skin feel, a biomimetic feel, high powder-grabbing power, and natural blending in a synthetic fiber brush. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 The flowchart illustrates the manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power, as provided by this invention. Detailed Implementation
[0019] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described in this specification are merely for explaining the invention and are not intended to limit the invention.
[0020] It should also be understood that the terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used in this specification and the appended claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise.
[0021] It should also be further understood that the term "and / or" as used in this specification and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes such combinations.
[0022] In an embodiment of the present invention, a makeup brush and its manufacturing process are provided that take into account both biomimetic touch and high powder-grabbing power. Through synergistic improvements in four aspects, namely fiber cross-sectional shape, surface microstructure, bristle length distribution and bristle density arrangement, the synthetic fiber bristles can simultaneously achieve the effects of softness and elasticity, high powder-grabbing power, concentrated coloring in the center and natural smudging at the edges.
[0023] Example 1 This embodiment provides a manufacturing process for a makeup brush that balances a soft feel against the skin with high powder-grabbing power, such as... Figure 1 As shown, the entire process flow includes fiber blending and irregular cross-section spinning, surface chemical etching treatment, multi-level length mixing of hair bundles, gradient density hair implantation and curing, tube pressing, low-temperature freezing and shaping, and cleaning and disinfection steps.
[0024] Step S1: Polybutylene terephthalate (PBT) is blended with polyamide (PA) and melt-spun to obtain fibers with a non-circular cross-section.
[0025] Specifically, the mass ratio of PBT to PA is controlled between 75:25 and 82:18, for example, 78:22. The two polymer chips are first dried in a vacuum drying tower at 120℃ to 140℃ for 4 to 6 hours to reduce the moisture content of the chips to below 80 ppm, thus avoiding high-temperature hydrolysis that could affect spinning stability and fiber quality.
[0026] The dried chips are fed into a screw extruder, with the melt temperature controlled at 250℃~280℃, for example, 265℃. The melt is precisely metered by a metering pump and extruded from a shaped spinneret. The spinneret's orifice cross-section is wavy or trilobal. The extruded nascent fibers are cooled and shaped under side-blown air conditions of 18℃~25℃ and 0.3m / s~0.6 m / s, followed by hot stretching. The stretching ratio is controlled at 3.2~4.0 times, for example, 3.6 times, and the stretching temperature is set at 80℃~120℃. After stretching, the diameter of the resulting fiber monofilament is controlled at 0.06mm~0.12mm, for example, 0.08mm.
[0027] It is important to emphasize here that non-circular cross-sections are not limited to wavy and trilobal shapes; they can also be cross-shaped, hollow, or other irregularly shaped cross-sections that can increase the specific surface area. To ensure the specific surface area gain of the non-circular cross-section, the fiber cross-section irregularity degree D = P can be defined. 2 / (4πA), where P is the perimeter of the fiber cross-section and A is the cross-sectional area of the fiber. When D=1, it is a circular cross-section; in this invention, it is preferred to control D≥1.2, more preferably D=1.3~1.5, to ensure that the specific surface area is increased by 15%~25% compared to a circular cross-section.
[0028] Therefore, by blending PBT with PA and using a specific stretching process, the fiber is endowed with good softness and resilience; the non-circular cross-section increases the specific surface area of the fiber, providing a larger effective contact area for subsequent chemical etching and powder adsorption, thereby improving powder gripping ability.
[0029] Step S2: Perform surface chemical etching on the fiber with a non-circular cross-section to form micropores with a depth of 0.2μm~1.0μm on the fiber surface and make its surface roughness 0.7μm~1.8μm.
[0030] In this embodiment, the treatment solution used for surface chemical etching contains, by mass percentage: 2wt%~4wt% (preferably 3wt%) sodium hydroxide, 0.3wt%~0.8wt% (preferably 0.5wt%) fatty alcohol polyoxyethylene ether, and 0.5wt%~1.2wt% (preferably 0.8wt%) γ-aminopropyltriethoxysilane, with the balance being deionized water. Fatty alcohol polyoxyethylene ether, as a penetrant and dispersant, promotes the uniform spreading of the etching solution on the fiber surface; γ-aminopropyltriethoxysilane, as a coupling agent, improves the affinity of the etched fiber surface for powder particles, thus helping to enhance powder adhesion.
[0031] During the immersion etching process, the fiber bundle is immersed in the aforementioned treatment solution. The temperature of the treatment solution is controlled at 65℃~75℃, preferably 70℃; the immersion time is controlled at 18min~30min, preferably 24min. During the immersion process, an ultrasonic generator can be activated at a frequency of 28kHz~40kHz and a power density of 0.5W / cm²~1.2 W / cm² to accelerate the removal of the etching product from the fiber surface and prevent localized over-etching.
[0032] In this step, the relationship between etching depth and immersion time and temperature satisfies the following empirical formula: In the formula, h is the average etching depth in μm; k is a preset constant related to the fiber material and alkali concentration; t is the immersion time in min; E aR is the apparent activation energy; T is the molar gas constant; and T is the absolute temperature in K. By controlling the temperature and time, the average etching depth is stabilized within the range of 0.2 μm to 1.0 μm. In this embodiment, the average etching depth is approximately 0.6 μm, and the surface roughness Ra is approximately 1.2 μm.
[0033] After etching, the fiber bundle is removed and washed twice in 50°C warm water for 3 minutes each time. Then, the residual alkali is neutralized with 0.5 wt% acetic acid aqueous solution, and then washed with deionized water until neutral. Finally, it is dried in a hot air drying oven at 60°C~70°C for 20~30 minutes until the moisture content is less than 1% (preferably less than 0.5 wt%).
[0034] Therefore, sodium hydroxide selectively hydrolyzes the ester and amide bonds in PBT and PA, forming uniformly distributed micropores on the fiber surface. The combined action of fatty alcohol polyoxyethylene ether and γ-aminopropyltriethoxysilane ensures uniform etching and improved surface affinity. The etched fiber surface forms micropores and protrusions resembling animal scales, increasing the mechanical binding force and van der Waals forces between powder particles and fibers, significantly enhancing powder gripping ability. Simultaneously, the etching depth is controlled at the sub-micron level, avoiding excessive damage to the fiber's inherent strength and maintaining a soft feel.
[0035] Step S3: Cut the chemically etched fibers into three groups of fibers of different lengths, mix them, comb them, and clump them together to form hair bundles with a length difference of 0.5 mm to 2.0 mm at the tip.
[0036] Specifically, the length and mass percentage of the three fiber groups are as follows: the long fiber group has a length of 35 mm to 38 mm and accounts for 50% to 60% of the total fiber mass; the medium fiber group has a length of 32 mm to 35 mm and accounts for 20% to 30% of the total fiber mass; and the short fiber group has a length of 28 mm to 32 mm and accounts for 15% to 25% of the total fiber mass. Preferably, the long fiber group has a length of 36 mm and accounts for 55% of the mass; the medium fiber group has a length of 33 mm and accounts for 25% of the mass; and the short fiber group has a length of 30 mm and accounts for 20% of the mass.
[0037] During mixing, the three groups of fibers are fed into an air-flow blending machine. The mixing time is controlled between 5 and 8 minutes, for example, 6 minutes; the mixing air velocity is 1.5 m / s to 2.5 m / s, for example, 2.0 m / s. Airflow mixing ensures that fibers of different lengths are evenly dispersed, preventing fibers of the same length from clumping together. The mixed fibers are then carded by a carding machine to make the fibers basically parallel, and then aligned at one end by a tufting device. Since the fibers of each group are of different lengths, a length difference naturally forms at the other end after one end is aligned. This length difference is adjusted by the mixing ratio and fiber bending stiffness, and the final effective length difference ΔL at the tip of the fiber bundle is controlled between 0.5 mm and 2.0 mm, preferably about 1.2 mm.
[0038] Therefore, by mixing three groups of fibers of different lengths in a specific ratio, the tips of the bristles naturally form a tapered shape, achieving a natural pointed tip similar to animal hair without the need for secondary trimming. This pointed tip structure improves the gradient distribution of powder on the bristles when applying powder, resulting in a more even and natural release, while also enhancing the soft feel of the brush head when in contact with the skin.
[0039] Step S4: Insert the bristle bundles into a mold with a pore array and a density that decreases from the center to the edge, and then dip the roots of the bristle bundles into moisture-curing polyurethane hot melt adhesive and cure it to form a brush head.
[0040] In this embodiment, the diameter of each hole in the hole array of the mold is 0.6~1.0 mm, preferably 0.8 mm. The radial distribution of the hole density satisfies the following formula: In the formula, ρ(r) is the pore density at a distance r from the center of the brush head, in units of pores / cm². 2 ;ρ c The pore density in the central area of the mold is 7~9 pores / cm³. 2 ;ρ e The pore density in the edge area of the mold is 4~5 pores / cm². 2 R is the equivalent radius of the brush head, in mm; n is the gradient exponent, ranging from 1 to 2.5. Preferably, ρ c Take 8 holes / cm 2 , ρ e Take 4.5 holes / cm 2 n is set to 1.5, and R is set to 12 mm. Using this density distribution function, the hair-embedded pore array smoothly decreases from the center to the edge, forming a gradient density arrangement.
[0041] During the hair implantation process, an automated hair implantation machine can be used to implant the hair tufts obtained in step S3 one by one into the holes of the mold. The implantation depth of the hair tufts in the mold is 4mm to 7mm, for example, 5.5mm. Before implantation, the roots of the hair tufts are pre-soaked in moisture-curing polyurethane hot melt adhesive with a layer thickness of 0.3mm to 0.5mm, for example, 0.4mm. This hot melt adhesive contains isocyanate groups and undergoes a cross-linking and curing reaction in the presence of moisture in the air.
[0042] The entire semi-finished hair bundle is then placed in a curing chamber at a curing temperature of 105℃~115℃, preferably 110℃; a relative humidity of 40%~60%, preferably 50%; and a curing time of 6min~10min, preferably 8min. During the curing process, water molecules in the air diffuse into the adhesive layer, initiating a reaction between isocyanate groups and water to form urea bonds and biuret cross-linked structures, resulting in a strong bond between the hair bundle root and the mold base. Testing showed that the pull-out force of a single hair bundle is ≥1.5 N.
[0043] It should be noted that the implementation of gradient density hair implantation is not limited to the density distribution function mentioned above; it can also be achieved by using a stepped decrease in zones (e.g., 8 holes / cm in the central zone). 2 6 holes / cm in the transition zone 2 4.5 pores / cm in the edge area 2 Alternatively, a smooth decreasing pattern can be used. The arrangement of the mold hole array can be concentric rings, honeycomb, or rectangular arrays, as long as the density decreases from the center to the edge.
[0044] Therefore, gradient density bristle planting results in dense bristles in the center of the brush head for concentrated powder pickup, while the bristles in the edge area are sparse for a softer release. Combined with the natural cone-shaped bristles formed by multi-level length mixing, this achieves a makeup effect of center color application and edge blending. The moisture-curing polyurethane hot melt adhesive fully cross-links under specific temperature and humidity conditions, ensuring a strong and reliable bristle root and low shedding rate.
[0045] Step S5: Press the brush head into the inlet tube, and then perform low-temperature freezing, shaping, cleaning, and disinfection to obtain the makeup brush.
[0046] When pressing the nozzle, an aluminum nozzle with an inner diameter matching the outer diameter of the nozzle base can be selected. The inner wall of the nozzle should be pre-knurled or coated with epoxy resin to increase friction after pressing. The nozzle should be preheated to 40℃~50℃, for example, to 45℃. Place the nozzle into the positioning fixture, ensuring the nozzle base is coaxial with the nozzle. Start the pressing machine with a pressing air pressure of 0.35MPa~0.55MPa and a holding time of 8s~12s. After pressing, the gap should be less than 0.05 mm, and it should not loosen when a 10 N axial tensile force is applied.
[0047] Specifically, during low-temperature cryogenic trimming, the brush head is placed in a freezer at -10℃ to 0℃ for 15 to 25 minutes. In this embodiment, the freezing temperature is -5℃ and the resting time is 20 minutes. Freezing reduces the mobility of fiber molecular chain segments and increases stiffness, making the fibers less prone to bending or splitting during trimming. Subsequently, a rotary cutter is used for trimming at a speed of 3000 rpm to 5000 rpm and a feed rate of 2 mm / s to 5 mm / s. Preferably, the speed is 4000 rpm and the feed rate is 3 mm / s, with a trimming error set to ≤±0.3 mm. The trimmed brush head can be flat, round, or beveled. After trimming, the brush head is placed at room temperature for 10 to 15 minutes to allow the fibers to regain their softness.
[0048] During cleaning and disinfection, ultrasonic cleaning is performed at a frequency of 28 kHz to 40 kHz for 2 to 4 minutes. In this embodiment, the ultrasonic frequency is 35 kHz, and the cleaning time is 3 minutes. The cleaning solution used contains 0.05 wt% to 0.1 wt% of a neutral surfactant. After cleaning, ozone disinfection is performed at a concentration of 5 ppm to 10 ppm for 30 minutes, for example, an ozone concentration of 8 ppm. Finally, the brush head is dried under hot air at 40℃ to 50℃ until the moisture content is below 0.5%, resulting in the finished brush head.
[0049] Therefore, the press-fitting of the nozzle ensures a firm and secure connection between the brush head and the nozzle; low-temperature freezing trimming ensures a neat brush head profile and high-quality tips, avoiding fiber splitting caused by room-temperature trimming; ultrasonic cleaning effectively removes trimming debris and residual impurities, while ozone disinfection kills bacteria and fungi, ensuring product hygiene and safety.
[0050] It is understood that the specific values in the above embodiments are merely examples, and those skilled in the art can adjust them according to actual needs. For example, the mass ratio of PBT to PA in step S1 can vary within the range of 75:25 to 82:18; different ratios will affect the softness and resilience of the fiber. A non-circular cross-section can also be selected as wavy or other irregularly shaped. The proportions of each component in the treatment solution in step S2 can be adjusted within a given range, and the combination of immersion temperature and time can be optimized according to the fiber material and the required etching depth. The length ratios of the three fiber groups in step S3 can be adjusted within a given range to obtain different tip tapers and hand feel. In step S4, the gradient index n can be selected between 1 and 2.5; the larger n is, the faster the density decreases from the center to the edge, and the softer the edge smudging. The combination of freezing temperature and time in step S5 can be fine-tuned according to the ambient temperature and fiber type.
[0051] Furthermore, in step S2, sodium hydroxide in the chemical etching solution can be replaced with other alkaline etching agents such as potassium hydroxide; fatty alcohol polyoxyethylene ether can be replaced with other nonionic surfactants; and γ-aminopropyltriethoxysilane can be replaced with other aminosilane coupling agents. In step S4, the moisture-curing polyurethane hot melt adhesive can also be replaced with other adhesives with moisture-curing properties, as long as they can fully cure and form a strong bond under given temperature and humidity conditions.
[0052] Example 2 The present invention also provides a makeup brush that combines a biomimetic feel with high powder-grabbing power, which is made by the above-mentioned manufacturing process. The specific process parameters and steps can be referred to the above content and will not be repeated here.
[0053] In summary, the makeup brushes manufactured using the above process combine a soft feel with high powder-grabbing power. Their non-circular cross-section fibers, after chemical etching, form a biomimetic microporous surface. Multi-level length mixing creates naturally pointed conical bristle bundles, and gradient density bristle planting achieves concentrated color application at the center and natural edge blending. Their overall performance is close to or even surpasses that of animal hair brushes. Tests show that, under the same conditions, powder pickup is more than 35% higher than ordinary round PBT brushes, the brush head has a ≥85% rebound rate after 50% compression, and the number of bristles shed after 100 cycles of rubbing on a standard test board is ≤3.
[0054] This invention is not limited to the descriptions and embodiments herein; therefore, other advantages and modifications can be readily realized by those skilled in the art. Thus, without departing from the spirit and scope of the general concept defined by the claims and their equivalents, this invention is not limited to the specific details, representative devices, and illustrative examples shown and described herein. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A manufacturing process for a makeup brush that combines a biomimetic tactile feel with high powder-grabbing power, characterized in that, Includes the following steps: S1. Polybutylene terephthalate is blended with polyamide and melt-spun to obtain fibers with a non-circular cross section. S2. Perform surface chemical etching on the fiber to form micropores with a depth of 0.2μm~1.0μm on the fiber surface, and make its surface roughness 0.7μm~1.8μm; S3. The fibers after surface chemical etching are cut into three groups of fibers of different lengths, mixed, combed and clumped together to form hair bundles with a length difference of 0.5 mm to 2.0 mm at the tip. S4. The bristle bundles are implanted into a mold with a pore array whose density decreases from the center to the edge. The roots of the bristle bundles are then dipped in moisture-curing polyurethane hot melt adhesive and cured to form a brush head. The pore density in the central region of the mold is 7-9 pores / cm², and the pore density in the edge region is 4-5 pores / cm². S5. Press the brush head into the inlet tube, and then perform low-temperature freezing, shaping, cleaning, and disinfection to obtain a makeup brush.
2. The manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power as described in claim 1, characterized in that, In step S1, the mass ratio of polybutylene terephthalate to polyamide is 75:25 to 82:18, the non-circular cross-section is wavy or trilobal, the melt spinning temperature is 250℃ to 280℃, and the stretching ratio is 3.2 to 4.0 times, so that the diameter of the obtained fiber monofilament is 0.06 mm to 0.12 mm.
3. The manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power as described in claim 1, characterized in that, In step S2, when performing surface chemical etching on the fiber, the treatment solution used contains, by mass percentage: 2wt%~4wt% sodium hydroxide, 0.3wt%~0.8wt% fatty alcohol polyoxyethylene ether, 0.5wt%~1.2wt% γ-aminopropyltriethoxysilane, with the balance being water; the immersion temperature is 65℃~75℃, and the time is 18min~30min; wherein, the average etching depth h satisfies the following relationship with the immersion time t and temperature T: In the formula, h is the average etching depth in μm; k is a preset constant related to the fiber material and alkali concentration; t is the immersion time in min; E a is the apparent activation energy; R is the molar gas constant; T is the absolute temperature in K.
4. The manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power as described in claim 1, characterized in that, In step S3, the length and mass percentage of the three groups of fibers are as follows: the length of the long fiber group is 35mm~38mm, accounting for 50%~60% of the total mass of the fiber bundle; the length of the medium fiber group is 32mm~35mm, accounting for 20%~30% of the total mass of the fiber bundle; and the length of the short fiber group is 28mm~32mm, accounting for 15%~25% of the total mass of the fiber bundle. The mixing time of the three groups of fibers is 5min~8min, and the mixing air velocity is 1.5m / s~2.5m / s. After mixing, the fibers are combed and tucked to form a fiber bundle.
5. The manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power as described in claim 1, characterized in that, In step S4, the diameter of each hole in the aperture array is 0.6 mm to 1.0 mm, and the radial distribution of the pore density satisfies: In the formula, ρ(r) is the pore density at a distance r from the center of the brush head, in units of pores / cm². 2 ; ρ c The pore density in the central region of the mold is 7~9 pores / cm³. 2 ; ρ e The pore density in the edge region of the mold is 4~5 pores / cm². 2 R is the equivalent radius of the brush head, in mm; n is the gradient exponent, ranging from 1 to 2.
5.
6. The manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power as described in claim 1, characterized in that, In step S4, the hair bundle is implanted into the mold at a depth of 4 mm to 7 mm, the root adhesive layer thickness is 0.3 mm to 0.5 mm, the curing temperature is 105℃ to 115℃, the relative humidity is 40% to 60%, and the curing time is 6 min to 10 min.
7. The manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power as described in claim 1, characterized in that, In step S5, the low-temperature freezing trimming includes: placing the brush head in a -10℃~0℃ freezing chamber for 15min~25min to stiffen the fibers; then trimming with a rotary cutter at a speed of 3000rpm~5000rpm and a feed speed of 2mm / s~5mm / s, with the trimming error set to ≤±0.3mm; and then warming up for 10min~15min after trimming.
8. The manufacturing process of the makeup brush that combines a biomimetic feel with high powder-grabbing power as described in claim 1, characterized in that, In step S5, the cleaning and disinfection includes: ultrasonic cleaning at a frequency of 28 kHz to 40 kHz for 2 min to 4 min, using a cleaning solution containing 0.05 wt% to 0.1 wt% of a neutral surfactant; then disinfecting with ozone at a concentration of 5 ppm to 10 ppm for 30 min; and finally drying under hot air at 40℃ to 50℃ until the moisture content is less than 0.5%.
9. A makeup brush that combines a biomimetic tactile feel with high powder-grabbing power, characterized in that, The makeup brush is manufactured using the process described in any one of claims 1-8, which combines a biomimetic feel with high powder-grabbing power.